A STUDY ON THE PRESENCE OF WORK- PLACE EMPLOYEE WELLNESS PROGRAM AND ITS EFFECTIVENESS WITH RESPECT TO THE WOMEN EMPLOYEES WORKING ACROSS MANU- FACTURING INDUSTRIES IN BANGALORE - Giribabu, N.; Jahnavi, K.N. (International Journal of Psychosocial Rehabilitation, 2020)
Indian industry is rapidly transforming into one of the worlds sought after a manufacturing hub as well as a service hub due to the strategic advantage it enjoys due to its diversified population, English language speak- ing people, availability of cheap labour and efficient manpower. India has the power to cater to the needs of the rest of the business world. The workforce is getting shifted from agricultural mode to industry and service mode in a notable manner. The manufacturing industry like the pharma sector, automobiles and the service industry like the IT and ITES industry, India is able to make itself mark compared to the rest of the world. The workforce increase has led to diversification of workforce and simultaneously the problems of workforce management has become a very big challenge. India has seen a significant industrial and service sector growth during the last 20- 25 years and has contributed in the upliftment of India’s image in the eyes of the rest of the world as a country having efficient and cheap manpower. Many view that this factor has empowered the women since there is a comparative increase in the number of women in the workforce which is a welcome factor. But there are findings that gives feedback that the attrition level of women employees is also high, added to that there are not many women working at the higher positions in most of the organizations. They face number of problems due to their gender. Just because of their gender, the women encounter unique set of challenges at their workplace. Most of these problems can be attended to and solved by having employee workplace welfare programs. This paper tries to find out across the organizations form all manufacturing industries if they have effective workplace employee wellness program that is beneficial to them. In case the company has the employee wellness program, then an attempt is made to find out to what extent it is effective. The paper also makes an effort to check the level of agreement on the fact that” Effective Employee Wellness program can reduce workplace challenges” of the women employees working across manufacturing industries, so that the organizations realise the significance and also the effectiveness of the employee wellness programs and check on the lacunae and work on it.